Bright Carbon Dots toward Cu and Fe Ion Sensing Mechanism and Application - Tian, Yi (Langmuir : the ACS journal of surfaces and colloids, 2025)
Copper and iron are essential elements for life, and their imbalance, or their excessively high concentrations, can lead to a range of serious issues, including neurodegenerative diseases, metabolic disorders, and environmental pollution. The development of efficient detection technologies is urgently required for water quality safety assessment, early disease diagnosis, and industrial process monitoring. Carbon dots (CDs) have gradually surpassed traditional quantum dots and organic dyes due to their unique photoluminescence properties, low environmental toxicity, and functionalizable surfaces, becoming a research focus in the field of metal ion sensing. Although significant progress has been made in the application of CDs for heavy metal detection in recent years, existing reviews have primarily focused on highly toxic ions such as mercury, lead, and chromium, with limited systematic summaries on the detection of copper and iron ions. This review focuses on the application of CDs in copper and iron ion detection, summarizing and categorizing the synthesis and modification methods of blue, green, and red fluorescent CDs, common quenching mechanisms, specific research progress in copper and iron ion detection using CDs, and the detection mechanisms of CDs that can simultaneously detect or differentially identify copper and iron ions. Finally, innovative research currently being conducted in the detection mode is introduced. This work aims to provide a reference for the synthesis and detection of CDs applied to copper and iron ion detection